2000
DOI: 10.1128/jvi.74.23.11055-11066.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vif in Stability of the Human Immunodeficiency Virus Type 1 Core

Abstract: The Vif protein of human immunodeficiency virus type 1 (HIV-1) is important for virion infectivity. Previous studies have shown that vif-defective virions exhibit structural abnormalities in the virus core and are defective in the ability to complete proviral DNA synthesis in acutely infected cells. We developed novel assays to assess the relative stability of the core in HIV-1 virions. Using these assays, we examined the role of Vif in the stability of the HIV-1 core. The integrity of the core was examined fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
65
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 70 publications
6
65
0
2
Order By: Relevance
“…Studies have suggested that either reverse transcription fails to proceed to completion or that reverse transcripts are unstable, possibly depending on the identity of the target cell (14,15,18,46,60,67). Correspondingly, several groups have found ⌬vif virions to be par-tially defective in endogenous reverse transcriptase (RT) assays (17,18,27,46,48). Whether these findings are indicative of a specific problem with the reverse transcription complex, structural abnormalities in the viral core (6,9,32,48), or some other molecular defect in virions is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that either reverse transcription fails to proceed to completion or that reverse transcripts are unstable, possibly depending on the identity of the target cell (14,15,18,46,60,67). Correspondingly, several groups have found ⌬vif virions to be par-tially defective in endogenous reverse transcriptase (RT) assays (17,18,27,46,48). Whether these findings are indicative of a specific problem with the reverse transcription complex, structural abnormalities in the viral core (6,9,32,48), or some other molecular defect in virions is unknown.…”
mentioning
confidence: 99%
“…Correspondingly, several groups have found ⌬vif virions to be par-tially defective in endogenous reverse transcriptase (RT) assays (17,18,27,46,48). Whether these findings are indicative of a specific problem with the reverse transcription complex, structural abnormalities in the viral core (6,9,32,48), or some other molecular defect in virions is unknown. To date, no reproducible quantitative or qualitative difference in the protein content of wild-type and ⌬vif virions has been reported, aside from a difference in Vif incorporation (6,11,22,38,39,42,61) and a controversial difference in Gag processing (6,56).…”
mentioning
confidence: 99%
“…Infection was measured 48 h after infection by performing luciferase assays (Promega). Infections of H9 or SupT1 cells were initiated by co-culture with virus-producing 293T cells (23). After overnight incubation, H9 or SupT1 cells were removed, washed, and cultured in RPMI medium with 10% fetal bovine serum.…”
mentioning
confidence: 99%
“…Viruses were quantitated by reverse transcriptase assays, and similar amounts were used to infect the reporter cell line Cf2-luc (23). Infection was measured 48 h after infection by performing luciferase assays (Promega).…”
mentioning
confidence: 99%
“…Proteaseprocessed Vif is believed to be an important step for production of infectious viruses [87]. Vif also stabilizes viral nucleoprotein complex through direct interaction with 5' region of HIV-1 genomic RNA [88][89][90][91]. Moreover, Vif modulates viral reverse transcriptase through its C-terminal domain either by stimulating the binding of RT and primer or increasing the polymerization rate of RT [92].…”
Section: Virus Infectivity Factor (Vif)mentioning
confidence: 99%